Analisis Kinerja Struktur Gedung Bertingkat Menggunakan Sistem Rangka Pemikul Momen Khusus (SRPMK) pada Pembangunan Rumah Susun Cakung Jakarta Timur - Hesty Auliya Dewi; Erno Widayanto; Ketut Aswatama Wiswamitra (Rekayasa Sipil, 2023)
Analysis of the structural performance of the Cakung house in East Jakarta aims to determine the behavior and performance of the building by using the Special Moment Bearing Frame system (SRPMK). Evaluation is carried out on the performance of the building structure by using a structural analysis aid program. And the lateral force capacity that the system can withstand is 1592432.05 Kgf in the X direction and 643948.61 Kgf in the Y direction. Where the pushover analysis using the ATC 40 method, the melting point occurred for the first time at a displacement of 23.57 cm in the X direction and 7.28 cm in the Y direction. And serious damage occurred at the displacement of 77.49 cm in the X direction and 94.84 in the Y direction. The analysis found that the drift ratio value of the maximum total deviation and the maximum inelastic deviation that occurs in the structure is less than 1%. So that the level of performance of the design is in the category of Immediate Occupancy (IO).